Autonomic regulation in athletic horses repetitively participating in two novice jumping classes on consecutive days - Wonghanchao, Thita; Huangsaksri, Onjira; Sanigavatee, Kanokpan; Poochipakorn, Chanoknun; Chanprame, Sarisa; Wongkosoljit, Sirapatch; Chotiyothin, Wanlapa; Rattanayanon, Nontaruj; Kiawwan, Ratsamin; Chanda, Metha (Frontiers in Veterinary Science, 2024)
IntroductionAnimal welfare is of great concern in equestrian sports and has been evaluated in athletic horses competing at different levels. However, the impact of consecutive days of jumping competition and the extent of resultant stress responses remains unclear. To address this point, the present study compared the changes in stress response via heart rate variability (HRV) in horses participating in two national jumping events on consecutive days.MethodsThe study involved six experienced horses equipped with heart rate monitoring devices. HRV variables were measured before, during, and after jumping at 10-min intervals for 60 min on each competition day.ResultsMultiple HRV variables decreased to varying degrees on both days from warm-up until 30 min post-jumping. Meanwhile, the mean heart rate increased during jumping and returned to normal levels at 50 min post-jumping on the first day (for all intervals, p < 0.05–0.001), while it remained elevated beyond 60 min post-jumping on the second day (for all intervals, p < 0.01–0.001). Additionally, maximum heart rate and respiratory rate were higher on the second day than in the first round during the warm-up phase (p < 0.05 for both variables). The proportion of the HRV low-frequency band was higher during riding on the second day (p < 0.05), while the proportion of the high-frequency band was reduced during warm-up on the first day (p < 0.05) and during course riding on the second (p < 0.01). Meanwhile, the sympathetic nervous system index took longer to return to baseline on the second day than on the first.DiscussionThese results suggest that autonomic regulation differed in horses between jumping rounds on two consecutive days, with horses experiencing higher sympathetic activity and potentially increased stress in the second round. This information is important for riders, highlighting the need to be mindful of potential stress that could, at least in part, impact the welfare of horses participating in the same jumping competition on consecutive days.